Respuesta :
No solution!
Explanation:
4x+4(-x)=-2
4x+(-4x)=-2
4x-4x=-2
0x=-2
0≠-2
therefore there is no solution to the system because the x value subtracts from itself and 0 is not equal to -2.
Hope this helps!
Explanation:
4x+4(-x)=-2
4x+(-4x)=-2
4x-4x=-2
0x=-2
0≠-2
therefore there is no solution to the system because the x value subtracts from itself and 0 is not equal to -2.
Hope this helps!
Solution:
Given that:
- y = -x
- 4x + 4y = -2
Substitute the value of y into equation #2.
- 4x + 4(-x) = -2
- 4x - 4x = -2
- 0 ≠ -2
Since the equation has no variable and is false, this system has no solution.